Application of Arduino smart MQ-2 sensor for early detection of gas influx in water base drilling fluids - Alowa, Mohammed E. Mehrez; Imbayyah Albusayifi; Omar Abudirbalah; Abdulaziz Ibrahim (Sebha University Conference Proceedings, 2025)
This study explores the predictive analysis of gas inflow events during drilling using water-based muds using sensors built into Arduino. Early detection of influx patterns is made possible by a specially designed monitoring system that uses the MQ-2 sensor and Arduino Uno to record real-time gas concentration data. The study shows that prediction models for upcoming gas kicks may be constructed by combining variations in mud properties (density and viscosity) with changes in gas sensors. This method presents a useful smart well control tool for field operations and training, and it represents a step forward in digitizing kick detection.